New evidence on the dynamic wage curve for Western Germany: 1980 - 2004 - Badi H. Baltagi; Uwe Blien; Katja Wolf (Institute for the Study of Labor (IZA), 2008)
In 1994, Blanchflower and Oswald reported that they have found an 'empirical law of economics' -the Wage Curve. According to their empirical results, the elasticity of wages with respect to regional unemployment is -0.1. This holds especially for the Anglo-Saxon countries. Our paper reconsiders the western German Wage Curve using disaggregated regional data and is based on a random sample of 974,179 employees drawn from the employment statistics of the Federal Employment Services of Germany (Bundesagentur für Arbeit) over the period 1980-2004. We find that the wage equation is highly autoregressive but far from unit root. This means that this wage equation is not a pure Phillips curve, nor a static Wage Curve, and one should account for wage dynamics. The unemployment elasticity is significant but relatively small: only between -0.02 and -0.04. We also check the sensitivity of this wage elasticity for different population groups (young versus old, men versus women, less educated versus highly educated, German native versus foreigner). We confirm that the wage elasticity is more flexible the weaker the bargaining power of the particular group.
urn:nbn:de:101:1-2008040982
Keywords: J30; 330; Wage curve; regional labour markets; Phillips curve; Lohnkurve; Regionale Lohnstruktur; Regionale Arbeitslosigkeit; Phillips-Kurve; Schätzung; Alte Bundesländer; Deutschland